Media Pembelajaran Berbasis Teknologi Informasi Dalam Meningkatkan Minat Belajar Akidah Akhlak di SD UMP Purwokerto - Nugroho, Tato; Fauzi, Fauzi (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to describe the application of learning media in increasing interest in learning Aqidah Akhlak in SD UMP Purwokerto students. This type of research is descriptive qualitative research. Data obtained through observation, interviews and documentation. The results showed that the use of audio-visual learning media was very supportive in learning activities, especially in learning Aqidah Akhlak. The students are very motivated when the learning uses google meet media, learning videos (youtube) and google forms. In addition, the use of learning media in SD UMP Purwokerto has an important role in students' interest in learning, including feelings of pleasure and increased interest in the material. The implication of this research is that teachers in delivering learning materials in class must be good at choosing the right media, teachers must have creative and innovative ideas so that the learning atmosphere of students is more enthusiastic and motivated.